The factors that lead to the non-enforcement of judgments in the contentious administrative processes on the payment of monetary obligations in the mixed courts of the Superior Court of Justice of Puno in 2012 - Stephanie Liz Cervantes Alagon (2020)
With the development of this research, the objective is to analyze the factors that lead to the non-enforcement of contentious-administrative judgments on payment of monetary obligations in the mixed courts of the Superior Court of Justice of Puno in 2012, the type of investigation corresponds to the descriptive-quantitative type, since it seeks to describe the facts in a single time according to the files analyzed, of which the too much procedural burden is reflected with respect to contentious administrative processes that contain the obligation to give sum of money, the same that they do not have an effective fulfillment of the sentence and are not reflected in reality and accordingly, propose alternative solutions that speed up the execution of judgments in contentious-administrative matters.